Functional training reduces body fat and improves functional fitness and cholesterol levels in postmenopausal women: A randomized clinical trial - Neves, Lucas M. [UNESP]; Fortaleza, Ana C. [UNESP]; Rossi, Fabrício E. [UNESP]; Diniz, Tiego A. [UNESP]; Codogno, Jamile S. [UNESP]; Gobbo, Luis A. [UNESP]; Gobbi, Sebastião [UNESP]; Freitas, Ismael F. [UNESP] (Edizioni Minerva Medica, 2017)
BACKGROUND: This randomized clinical trial with concealed allocations, and blinding of the assessors and the data analyst, was aimed at determining the effects of 16 weeks of functional training on the body composition, functional fitness and lipid profiles in postmenopausal women. METHODS: The study began with 64 subjects (N.=32 functional training and N.=32 control group) and ended with 50 subjects (N.=28 functional training and N.=22 control group). The exercise was conducted in circuit training format with 8 stations related to the development of muscular strength (using elastic bands for resistance) plus 3 stations focused on balance, coordination, and agility. The training session also incorporated an 18 to 30 minute walk. The control group did not participate in the exercise programs during the period of study. The participants were evaluated before and after the training period as regards their body composition (fat and lean mass), functional fitness, abdominal strength and blood chemistry variables. RESULTS: Significant reductions were observed in all body composition variables related to fat (FM=-3.4 and Android FM=-7.7%) (P<0.05). The functional fitness components had significant improvements in coordination (-33.3%), strength (66.5%), agility (-19.5%) and aerobic capacity (-7%), and significant improvement in abdominal strength (188.2%). We observed significant improvements in total cholesterol (-4.4%) and HDL (-9.9%). CONCLUSIONS: The observed data lead us to conclude that functional training utilizing with elastic bands and unstable bases causes significantly improved in body composition, functional fitness and lipid profiles.
Keywords: Adipose tissue; Exercise; Menopause; Women